Disinfection Kinetics of Free Chlorine, Monochloramines and Chlorine Dioxide on Ammonia-Oxidizing Bacterium Inactivation in Drinking Water - Yongji Zhang (MDPI AG, 2021)
With the widespread use of chloramines disinfection, nitrification has become a problem that cannot be ignored. In order to control nitrification in the drinking water distribution system (DWDS), the inactivation effect of free chlorine, monochloramine and chlorine dioxide on ammonia-oxidizing bacterium (AOB) was studied under different temperature (8 °C, 26 °C and 35 °C) and pH (6.0, 7.0 and 8.7) conditions. The inactivation effect of Nitrosomonas europaea (a kind of AOB) by the three disinfectants increases with increasing temperature. As for the raised pH, the inactivation effect of free chlorine and monochloramine on AOB decreased, while that of chlorine dioxide increased. Last, but certainly not least, the experimental data of the disinfection were calculated to develop the N. europaea inactivation kinetic model, which was based on the first order Chick–Watson equation. The proposed model in this study took the two variables, pH and temperature, into consideration simultaneously, which were used to evaluate the average Ct value (multiplying the concentration of the residual disinfectant by the time of contact with N. europaea) required for different disinfectants when they produced the ideal inactivation effect on N. europaea.